A complex proinflammatory cascade mediates the activation of HSCs upon LPS exposure in vivo - Demel, Uta; Lutz, Raphael; Sujer, Stefanie; Demerdash, Yasmin; Sood, Shubhankar; Grünschläger, Florian; Kuck, Andrea; Werner, Paula Sophie; Blaszkiewicz, Sandra; Uckelmann, Hannah Julia; Haas, Simon; Essers, Marieke (Blood advances, 2022)
Infections are a key source of stress to the hematopoietic system. While infections consume short-lived innate immune cells, their recovery depends on quiescent hematopoietic stem cells (HSCs) with long-term self-renewal capacity. Both chronic inflammatory stress and bacterial infections compromise competitive HSC capacity and cause bone marrow (BM) failure. However, our understanding of how HSCs act during acute and contained infections remains incomplete. Here, we used advanced chimeric and genetic mouse models in combination with pharmacological interventions to dissect the complex nature of the acute systemic response of HSCs to lipopolysaccharide (LPS), a well-established model for inducing inflammatory stress. Acute LPS challenge transiently induced proliferation of quiescent HSCs in vivo. This response was not only mediated via direct LPS-TLR4 conjugation on HSCs but also involved indirect TLR4 signaling in CD115+ monocytic cells, inducing a complex proinflammatory cytokine cascade in BM. Downstream of LPS-TLR4 signaling, the combined action of proinflammatory cytokines such as interferon (IFN)α, IFNγ, tumor necrosis factor-α, interleukin (IL)-1α, IL-1β, and many others is required to mediate full HSC activation in vivo. Together, our study reveals detailed mechanistic insights into the interplay of proinflammatory cytokine-induced molecular pathways and cell types that jointly orchestrate the complex process of emergency hematopoiesis and HSC activation upon LPS exposure in vivo.